FR1.2: Women's Empowerment and Livestock Vaccination: evidence from PPR vaccination interventions in northern Ghana - Omondi, Immaculate A.; Galiè, Alessandra; Teufel, Nils; Loriba, Agnes; Kariuki, Eunice; Baltenweck, Isabelle (International Livestock Research Institute, 2022)
Healthy livestock provide meaningful opportunities to enhance women's empowerment in low- and middle-income countries. Animal vaccines are important to keep livestock healthy and productive. However, gender-based restrictions limit women's access to animal health services, thereby affecting the potential of livestock to enhance their empowerment. While growing empirical evidence reveals that women-controlled livestock (for instance, small ruminants) have important implications for women's empowerment and support better household nutrition outcomes, little empirical evidence exists from rigorous analyses of the relationship between women's empowerment and animal vaccines for women-controlled livestock species. Our analysis explores the relationship between women's empowerment and involvement with Peste des Petits Ruminants (PPR) vaccination in Ghana. Data collected using the Women's Empowerment in Livestock Index tool from 465 women and 92 men farmers (who keep goats) from northern Ghana, analyzed using Partial Least Squares Structural Equilibrium Model, revealed a significant direct positive association between knowledge about animal health and PPR vaccines and a significant indirect positive association between access to PPR vaccines and empowerment. A few, not all, indicators of empowerment, jointly and significantly explained empowerment of women goat farmers as far as the relationship between empowerment and vaccine facets is concerned. The significant indicators were "asset ownership" and "input into decisions" concerning livestock. These study results reveal important considerations in designing effective and equitable livestock vaccine systems.